2016
DOI: 10.1128/jcm.02635-15
|View full text |Cite
|
Sign up to set email alerts
|

Does the Capsule Interfere with Performance of Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry for Identification of Cryptococcus neoformans and Cryptococcus gattii?

Abstract: We described the impact of the capsule size for Cryptococcus neoformans and Cryptococcus gattii identification at the species level by Bruker matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). After experimental capsule size modulation, we observed that reducing the capsule size resulted in improved identification by Bruker MALDI-TOF MS across all of the reference strains analyzed. Cryptococcus neoformans and Cryptococcus gattii are relevant species among the pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Unreliable identification of C. neoformans by the Biotyper has been reported (identification rates of 50–66%) [ 7 17 18 ]. This may be due to the polysaccharide capsule of this pathogen, which renders the extraction and solubilization of proteins difficult, or due to insufficient database entries that would enable spectral matches [ 19 ]. We confirmed that the Biotyper system has some difficulties identifying C. neoformans when using direct FA extraction, and that an improved rate of the identification of C. neoformans isolates can be observed following the FA/ACN extraction, as reported previously [ 7 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unreliable identification of C. neoformans by the Biotyper has been reported (identification rates of 50–66%) [ 7 17 18 ]. This may be due to the polysaccharide capsule of this pathogen, which renders the extraction and solubilization of proteins difficult, or due to insufficient database entries that would enable spectral matches [ 19 ]. We confirmed that the Biotyper system has some difficulties identifying C. neoformans when using direct FA extraction, and that an improved rate of the identification of C. neoformans isolates can be observed following the FA/ACN extraction, as reported previously [ 7 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growth on some media may yield low scores/percentages [75], and small or mucoid colonies may fail. Using experimental capsule size manipulation, it was demonstrated that capsule size of C. neoformans and C. gattii can compromise identification by the Bruker system [76]. Refined interpretive criteria may be needed to discriminate closely related species and distinguish them from the next best taxon match.…”
Section: Limitationsmentioning
confidence: 99%
“…Correct identification percentage values obtained by authors studying the application of this identification method with regard to Cryptococcus ranged from 0 to 100% 64 68 . The differences in the observed values depended mainly on the strain tested (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…The method enables rapid and reproducible identification and can be applied to a vast range of microorganisms. Though several authors reported the usefulness of this technique in the recognition of CNGSC at the species and even sub-species level, it was also observed that the presence of the capsule as well as the cell wall composition, make MALDI-TOF MS identification of these pathogens challenging in comparison to other clinically important fungal agents 63 , 64 . Additionally, it was noticed that in some of the manufacturer’s library versions, spectra of particular types belonging to the CNGSC were underrepresented, therefore construction of the in-house libraries were beneficial for the increase in identification quality 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%